2023
DOI: 10.3389/fmicb.2023.1229828
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric bacteria: the key to sustainable heavy metal detoxification strategies

Abstract: The increasing rate of industrialization, anthropogenic, and geological activities have expedited the release of heavy metals (HMs) at higher concentration in environment. HM contamination resulting due to its persistent nature, injudicious use poses a potential threat by causing metal toxicities in humans and animals as well as severe damage to aquatic organisms. Bioremediation is an emerging and reliable solution for mitigation of these contaminants using rhizospheric microorganisms in an environmentally saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 227 publications
(211 reference statements)
0
5
0
Order By: Relevance
“…These could be ascribed to the direct release of nutrients from organic fertilizers and biochar ( Hussain et al, 2023 ). Furthermore, the improvements in available soil nutrients could be attributed to the high alkalinity and cation exchange capacity (CEC) of biochar ( Muhammad et al, 2018 ; Joshi et al, 2023 ; Xiao et al, 2023 ). Nevertheless, it is important to note that although BO treatment mitigated Cd accumulation in Sophora tissues, complete avoidance of Cd absorption was not achieved ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could be ascribed to the direct release of nutrients from organic fertilizers and biochar ( Hussain et al, 2023 ). Furthermore, the improvements in available soil nutrients could be attributed to the high alkalinity and cation exchange capacity (CEC) of biochar ( Muhammad et al, 2018 ; Joshi et al, 2023 ; Xiao et al, 2023 ). Nevertheless, it is important to note that although BO treatment mitigated Cd accumulation in Sophora tissues, complete avoidance of Cd absorption was not achieved ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the activities of diverse soil enzymes, which are crucial for facilitating the circulation of matter and energy in the soil, are valuable indicators of soil health ( Yao et al, 2018 ; Chow and Pan, 2020 ; Yan et al, 2022 ; Joshi et al, 2023 ). Compared with the HM and FS groups, BO treatment significantly induced the activities of multiple soil enzymes, including catalase, polyphenol oxidase, and β-glucosidase ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rhizospheric bacteria, in addition to plants, play a critical role in the process of cleaning up contaminated environments. The same principles of phytoremediation that nature utilizes are employed by microorganisms and plants to decrease organic and inorganic contaminants . While previous studies have demonstrated the potential of nanophytoremediation of soil pollutants, newer dimensions emphasize a deeper understanding of uptake mechanisms, enhanced plant–microbe interactions, tailored nanoparticle design, multicontaminant remediation, green synthesis, field-scale applications, risk assessment, and community engagement.…”
Section: Remediation Of Heavy Metals Using Nanotechnologymentioning
confidence: 99%
“…The same principles of phytoremediation that nature utilizes are employed by microorganisms and plants to decrease organic and inorganic contaminants. 97 While previous studies have demonstrated the potential of nanophytoremediation of soil pollutants, 98 newer dimensions emphasize a deeper understanding of uptake mechanisms, enhanced plant–microbe interactions, tailored nanoparticle design, multicontaminant remediation, green synthesis, field-scale applications, risk assessment, and community engagement. These insights will contribute to the ongoing development of effective and sustainable nanophytoremediation strategies for diverse soil pollution challenges.…”
Section: Remediation Of Heavy Metals Using Nanotechnologymentioning
confidence: 99%
“…The cellular structure of PGPB enables it to capture heavy metal ions and absorb them at binding sites on the cell wall. Negatively charged sulfhydryl, carboxyl, hydroxyl, sulfonic, amino, and amide groups on the cell surface bind to positively charged HMs, fixing them onto the cell surface [229]. Some PGPB also produce biosurfactants, such as lipopeptide, subtilisin, and rhamnolipid, which form complexes with HMs [230].…”
Section: Decrease In the Bioavailability Of Heavy Metalsmentioning
confidence: 99%